Underwater Archaeological Museum: Utilization of Karimunjawa Sites - Putranto, St. Prabawa Dwi; Munandar, Agus Aris (Universitas Muhammadiyah Surakarta, 2016)
Indonesia is located in a strategic location between Indian and Pacific Ocean. Indonesia has water territory more than land territory with approximately 3:2 in ratio. In that vast area, there are many cultural heritages from old history, both in land and underwater. Cultural heritages found in both locations have a connection. Until recently, the government has attempted to reveal the past from underwater cultural heritage through survey and exploration. Many invaluable cargoes were salvaged from the underwater wreckages. Exploration and salvage are done by private company with the permit from the National Committee for Salvage and Utilization of the Valuable Object of the Sunken Ship (PANNAS BMKT). However, illegal exploration and salvage persists in the practice. Conservation efforts that include protection, development and utilization to the underwater cultural heritage had not been maximal; therefore, salvage, pilferage, and vandalism still occur. This paper would try to give an alternative for the utilization of underwater cultural heritage through a maritime museum in its natural state (in-site conservation). Museum is one institution that protects, develops and utilizes cultural heritages, and communicates them to the visitor.